2018
DOI: 10.3389/fphys.2018.00041
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Functionality of Transfused Red Blood Cells in the Microcirculation of Blood Recipients

Abstract: The primary goal of red blood cell (RBC) transfusion is to supply oxygen to tissues and organs. However, due to a growing number of studies that have reported negative transfusion outcomes, including reduced blood perfusion, there is rising concern about the risks in blood transfusion. RBC are characterized by unique flow-affecting properties, specifically adherence to blood vessel wall endothelium, cell deformability, and self-aggregability, which define their hemodynamic functionality (HF), namely their pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 83 publications
(103 reference statements)
0
20
1
2
Order By: Relevance
“…These studies suggested that patients who had microcirculatory disturbances prior to transfusion benefited from the transfusion, showing a significant improvement in tissue oxygenation or microcirculatory flow indices. Conversely, patients who had relatively normal microcirculation showed either no improvement or a decline after transfusion [19]. In the present study, a transfusion of 1 unit of RBCs corrected dilutional anemia resulting from CPB; however, global indices of tissue oxygenation have shown more of a decline in hemodiluted and transfused patients than in patients who did not develop dilutional anemia and were not transfused.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…These studies suggested that patients who had microcirculatory disturbances prior to transfusion benefited from the transfusion, showing a significant improvement in tissue oxygenation or microcirculatory flow indices. Conversely, patients who had relatively normal microcirculation showed either no improvement or a decline after transfusion [19]. In the present study, a transfusion of 1 unit of RBCs corrected dilutional anemia resulting from CPB; however, global indices of tissue oxygenation have shown more of a decline in hemodiluted and transfused patients than in patients who did not develop dilutional anemia and were not transfused.…”
Section: Discussioncontrasting
confidence: 72%
“…The modulation of vascular function in opposing ways by activating nitric oxide (NO) production or releasing free hemoglobin, which is a scavenger of NO, is another explanation for the different study findings about the efficacy of transfusions. The presence of white blood cells in the transfused units may also have an important role in the adverse effects observed in patients [7,19]. In order to minimize these various effects, RBCs that had been stored for fewer than 10 days were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with beta thalassemia major, in which a genetic mutation results in significantly reduced beta‐globin production, also produce RBCs with reduced deformability . This leads to severe anemia and subsequent dependence on RBC transfusions that may alter the patient's hemodynamic environment . Furthermore, in transfusion medicine, physical modification and degradation of RBCs (storage lesion) is known to occur when stored in blood banks due to accumulation of microparticles and alterations in the plasma membrane structure of the stored RBCs .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, similar to the effect of reduced vessel caliber, higher blood viscosity contributed to by impaired RBC deformability would increase local resistance to blood flow, leading to the downstream cascade of events that result in diabetic microangiopathy. The direct relation between RBC deformability and the microcirculation impairment has been alluded to in several studies, 20,56‐58 although there has only been a handful of empirical evidence of this. Sosa et.…”
Section: Discussionmentioning
confidence: 99%